2021
DOI: 10.1021/acsinfecdis.1c00175
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of New Quinazolin-4(3H)-one Derived PqsR Antagonists as Quorum Sensing Quenchers in Pseudomonas aeruginosa

Abstract: P. aeruginosa (PA) continues to pose a threat to global public health due to its high levels of antimicrobial resistance (AMR). The ongoing AMR crisis has led to an alarming shortage of effective treatments for resistant microbes, and hence there is a pressing demand for the development of novel antimicrobial interventions. The potential use of antivirulence therapeutics to tackle bacterial infections has attracted considerable attention over the past decades as they hamper the pathogenicity of target microbes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…Until now, very few studies showed the effect of QS inhibitors on CF clinical isolates ( Rampioni et al, 2017b ; D’Angelo et al, 2018 ; Baldelli et al, 2020 ; Mahan et al, 2020 ; Papa et al, 2021 ; Soukarieh et al, 2021 ), and only in one study the antivirulence activity of a drug targeting the las QS system, furanone C-30, was tested in a collection of fifty CF isolates, revealing highly variable response and high frequency of resistance to the QS inhibitor in CF isolates ( García-Contreras et al, 2015 ), in overall accordance with this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Until now, very few studies showed the effect of QS inhibitors on CF clinical isolates ( Rampioni et al, 2017b ; D’Angelo et al, 2018 ; Baldelli et al, 2020 ; Mahan et al, 2020 ; Papa et al, 2021 ; Soukarieh et al, 2021 ), and only in one study the antivirulence activity of a drug targeting the las QS system, furanone C-30, was tested in a collection of fifty CF isolates, revealing highly variable response and high frequency of resistance to the QS inhibitor in CF isolates ( García-Contreras et al, 2015 ), in overall accordance with this study.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, since the las QS system is hierarchically dominant over the rhl and pqs system in P. aeruginosa reference strains, the research of QS inhibitors has been targeted mainly toward this system ( Rampioni et al, 2014 ; Soukarieh et al, 2018a ). However, several studies reported the identification of molecules targeting the pqs system, including: metilantranilate ( Calfee et al, 2001 ); farnesol ( Cugini et al, 2007 ); halogenated anthranilic acid ( Lesic et al, 2007 ); quinazolidine derivatives ( Ilangovan et al, 2013 ; Soukarieh et al, 2018b , 2021 ); benzamide-benzimidazole ( Starkey et al, 2014 ; Maura and Rahme, 2017 ); pimozide ( Mellini et al, 2019 ); nitrofurazone and erythromycin estolate ( Baldelli et al, 2020 ); 2-sufonylpyrimidines ( Thomann et al, 2016a , b ). Compared with these anti- pqs drugs, clofoctol has the advantage of being already used in humans for the treatment of pulmonary infections, hence the delivery of this drug to the CF clinical setting should in principle be more straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Docking of PQS gave a predicted binding energy (E bind ) of −8.1 kcal•mol −1 for the best pose, in which PQS is deeply bonded in the B pocket (Figure 3B), through hydrophobic interactions with the residues Ala102, Ile149, Ala168, and Pro238, contrary to NHQ which occupies the two pockets (Figure 3A). As expected, PQS interactions were mainly hydrophobic [25,29,30]. Our docking results showed PQS forms several H-bonds between its carbonyl group and Gln194 and Ser196, and between its 3-hydroxyl group and Leu197.…”
Section: Docking Of Chromone 2-carboxamides With Pqsrsupporting
confidence: 76%
“…Kinetic studies using pqsR mutants proved that the pqs system is involved in early steps of biofilm formation and supported the fact that it represents an interesting target for new anti-virulence and antibiofilm compounds against P. aeruginosa pathogenicity [27,29,30,48,49]. Regarding the crucial role of the pqs system in the adaptability of P. aeruginosa, including biofilm formation, virulence regulation and some remarkable secondary effects, like iron acquisition or cytotoxicity [26,50,51], we chose an anti-biofilm assay based on detection of adherent cell population, rather than the classically used crystal violet method, suitable for the evaluation of total biomass but nonspecific enough [52].…”
Section: Anti-biofilm Activity Against P Aeruginosamentioning
confidence: 74%
“…Docking studies suggested that an interaction via a hydrogen bond is possible between the carbonyl function at position 4 of the quinazolone ring and the hydroxyl group of Thr265 as for the 2-alkyl-quinazolone derivative 31. In 2021, Grossman's group described a new quinazolone derivative as a PqsR antagonist (IC 50 of 1.1 µM in a P. aeruginosa PAO1-L strain) with an anti-pyocyanin activity similar to compounds 32 and 33 (80% of inhibition at 3 µM in a P. aeruginosa PAO1-L strain) [111].…”
Section: Ilangovan Et Al Studied the Interactions Of Hhq Pqs And Othe...mentioning
confidence: 99%